Biomechanical Impact of FHL Tendon Harvest on Forefoot and Great Toe Push-off Strength and Its Correlation to Knot of Henry Crossover Variation. Issue 3 (14th September 2018) - Charlton, Timothy; Thomas, Danielle; Thordarson, David; Metzger, Melodie; Nelson, Trevor
Category: Midfoot/Forefoot Introduction/Purpose: The flexor hallucis longus (FHL) tendon is commonly used for tendon transfers in reconstructive Achilles tendon procedures. A subset of patients who undergo this procedure complain of first great toe weakness and loss of push off strength after FHL tendon transfer. Despite the frequency of this procedure, there is currently little information available to surgeons to help understand this potential complication. Therefore, the objective of this biomechanical cadaveric study was to quantify plantar flexion strength after FHL harvest and correlate it to variations in anatomy to determine if distinct tendon crossover patterns at the Knot of Henry are more likely to lead to forefoot weakness. Methods: Cadaveric specimens were procured from an approved tissue bank. The proximal end of the tibia was potted and secured to the Mechanical Testing System. A pressure mapping system was used to measure plantar force though the great toe and lesser toes. The Achilles, FHL, and flexor digitorum longus (FDL) tendons were attached to linear actuators for load application. Pressure under the toes was measured with the Achilles alone, Achilles with FHL, Achilles with FDL, and Achilles with both FHL and FDL. The resultant loading patterns were recorded in the greater and lesser toes and compared between the different states. After biomechanical testing, all specimens were carefully dissected and the tendinous slips between the FHL and FDL were documented and classified based on a previously determined system (Types I-V, LaRue; Edama) Functional and anatomical relationship between the classification type and loading patterns were statistically analyzed using repeated measures ANOVA. Results: 23 specimens (13M / 10F) with a mean age of 71 years (range: 54-90) were used in this study. 61% were anatomically classified as type I, followed by type II (26%), IV (9%), and type V (4%), and type III (0%). Simulated FHL harvest in type I specimens resulted in a 29% decrease in great toe flexion pressure and an 21% decrease in total forefoot flexion pressure, p<0.05. In type II feet, FHL harvest led to a greater reduction in flexion pressure in the great toe (34%) and forefoot (25%), p<0.05. Type IV specimens also had a decrease in flexion pressure in both the great toe (21%) and forefoot (15%), p<0.05. Type V specimens trended similar to type I specimens. Conclusion: This study is the first to quantify loss of great toe and lesser toe flexion pressure after FHL harvest. In addition, it is the first to correlate these losses to variations in anatomic crossover patterns at the Knot of Henry. Specimens classified as type II had the greatest reduction in flexion pressure, followed by type I and type IV. This information is clinically important for preoperative discussions about post-surgical expectations and surgical planning.